Latin America : management education's growth and future pathways - e uthor; Thomas, Howard; Thomas, Lynne; Wilson, Alexander (Alexander David) (Emerald Publishing Limited, 2018)
Latin American business schools have grown in scale and quality in recent decades, yet they have received a relatively low level of attention globally when compared to schools from other parts of the world. This book seeks to address this dearth of attention and provide an in-depth examination of management education in the region. The book examines the main historical, cultural, social, political, and economic aspects of the Latin American continent and describes the evolutionary path of business education in the region until its current state. It analyzes and interprets the major events, key issues, impact of different actors, main changes, and "blind spots" in the evolution of management education in Latin America over the last 10 years. It then identifies the biggest on-going challenges confronting business education on the continent and discusses whether a Latin American model for management education is a realistic proposition. Finally, the book explores how the competitive environment of business education in the region will evolve over the next 10 years, and how these changes will influence the critical issues facing Latin American management education.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Business schools -- Latin America; Education -- Latin America; Business & Economics -- Education; Business studies: general